Seni, Gerbang Cakrawala Munculnya Postmodernisme - I Nyoman Chaya (Greget, 2012)
Post-modernism appears as a critique of the worldview splendor which is more modernism with an open horizon and critical thinking in order to find a new meaning of a â€œtruthâ€ thatÂ scrutinized from the phenomena of human life. The horizon boundary of post-modernism, which emerges the natural limits of modernist thoughts, makes the post-modern thinking that beyond the region denies the rationality. Regard to this, the art world long before had built a discourse aboutÂ the meaning of life entrenched struggle involving taste and feeling that goes through the edge ofÂ imaginary territory. Art, then, inspires and opens the gate so that it establishes the horizon ofÂ philosophical dictum of postmodernism. Keywords : arts, modern, postmodern